2012
DOI: 10.1088/0957-4484/23/49/495201
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence enhancement from nano-gap embedded plasmonic gratings by a novel fabrication technique with HD-DVD

Abstract: We demonstrate strong electromagnetic field enhancement from nano-gaps embedded in silver gratings for visible wavelengths. These structures fabricated using a store-bought HD-DVD worth $10 and conventional micro-contact printing techniques have shown maximum fluorescence enhancement factors of up to 118 times when compared to a glass substrate under epi-fluorescent conditions. The novel fabrication procedure provides for the development of a cost-effective and facile plasmonic substrate for low-level chemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 63 publications
1
60
0
Order By: Relevance
“…2 and further described in the Experimental section. 12 As the gratings were fabricated using the xed patterns of the HD-DVD, the capability to change the height, pitch and duty cycle of the polymer layer (PMSSQ) was limited. To study the effect of various parameters discussed above on light coupling and concentration, our novel approach was to control the surface energy of the polymer layer, deposition method (RF sputtering vs. thermal evaporation), and the use of different adhesion layers (chromium (Cr) for thermal evaporation, germanium (Ge) or titanium (Ti) for sputtering).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 and further described in the Experimental section. 12 As the gratings were fabricated using the xed patterns of the HD-DVD, the capability to change the height, pitch and duty cycle of the polymer layer (PMSSQ) was limited. To study the effect of various parameters discussed above on light coupling and concentration, our novel approach was to control the surface energy of the polymer layer, deposition method (RF sputtering vs. thermal evaporation), and the use of different adhesion layers (chromium (Cr) for thermal evaporation, germanium (Ge) or titanium (Ti) for sputtering).…”
Section: Resultsmentioning
confidence: 99%
“…The formation of SPR on a metallic grating is commonly seen as a sharp dip in the reectivity at particular wavelengths and angles of incidence. 12,26 The depth of the reectivity dip, also called the coupling strength (s), is an indicator for how strongly light is coupled to the grating while full width at half maximum (FWHM) indicates the range of wavelengths that can couple at a particular angle of incidence. The reectivity of the different grating samples has been plotted in Fig.…”
Section: Surface and Optical Characterizationmentioning
confidence: 99%
“…Careful engineering of the geometries of the inverse pyramids in these substrates enables tuning of the plasmon modes to be resonant with excitation wavelengths in the red and near infra-red regions 20 . Similarly, the uniform grating patterns on the surfaces of optical discs can give rise to surface localized plasmons that can enhance Raman signals with choice of appropriate excitation wavelengths [27][28][29][30] . However, for the BD-R the gratings on the surface are spaced around 320 nm apart and no coupling of the surface plasmons can occur with the 785 nm excitation wavelength.…”
Section: Results and Duscussionmentioning
confidence: 99%
“…Previous studies have shown that the periodic, uniform nanostructured surfaces of optical discs (compact discs (CDs) and digital versatile discs (DVDs) coated with thin metal films 24-27 provide very good, inexpensive SERS substrates. The uniform grating patterns on the surfaces of CDs and DVDs can enable coupling of surface plasmons with the laser excitation to provide intense localised electromagnetic radiation which can enhance the Raman signals [27][28][29][30] .…”
Section: Introductionmentioning
confidence: 99%
“…Plasmonically excited Raman scattering (SERS) and fluorescence sensors from metallic nanoparticles (NPs) or surfaces have enhanced the sensitivity of optical molecular sensors by orders of magnitude. [6][7][8][9] However, probe-less SERS sensing or fluorescent sensing of unlabeled targets are insufficiently specific for miRNA targets in heterogeneous samples. Plasmonic detection is also very compatible with FRET probes whose donor dye offers small light sources to excite fluorescently labelled targets upon hybridization.…”
mentioning
confidence: 99%